2013
DOI: 10.1128/jcm.03192-12
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Mycobacterium tuberculosis Rv1681 Protein as a Diagnostic Marker of Active Pulmonary Tuberculosis

Abstract: The development of an accurate antigen detection assay for the diagnosis of active tuberculosis (TB) would represent a major clinical advance. Here, we demonstrate that the Mycobacterium tuberculosis Rv1681 protein is a biomarker for active TB with potential diagnostic utility. We initially identified, by mass spectroscopy, peptides from the Rv1681 protein in urine specimens from 4 patients with untreated active TB. Rabbit IgG anti-recombinant Rv1681 detected Rv1681 protein in lysates and culture filtrates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…During infection, Mycobacterium-specific proteins, peptides, DNA, and lipids are released into the circulation (14,15) and are likely to provide unprecedented specificity to identify M. bovis infection. We hypothesized that a panel of biomarkers, including host and pathogen peptides, would establish a precise test to detect subclinical bTB infection.…”
mentioning
confidence: 99%
“…During infection, Mycobacterium-specific proteins, peptides, DNA, and lipids are released into the circulation (14,15) and are likely to provide unprecedented specificity to identify M. bovis infection. We hypothesized that a panel of biomarkers, including host and pathogen peptides, would establish a precise test to detect subclinical bTB infection.…”
mentioning
confidence: 99%
“…Recently, the Campos-Neto group reported the identification of TB antigens in urine samples, but the biomarker reportedly fell short of its expected performance. with a diagnostic sensitivity of less than 50% (4).…”
mentioning
confidence: 98%
“…The presence of a peptide of molybdenum import ATPbinding protein (ModC) was also validated in three out of five independent urine samples by a multiple reaction monitoring (MRM) method. It should be noted that ModC is a protein involved in the metabolism of molybdenum ion, and a molybdenum-associated antigen (MoaA-related protein) was also identified by an independent group (3,4). Figure S3 in the supplemental material shows the tandem mass spectrometry spectrum of a ModC peptide with a molecular ion mass of 464.24 m/z (ϩ2) and a peptide sequence of QLSGGQAQR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, KASHINO et al [13] used one-dimensional LC combined with MS/MS to identify four M. tuberculosis-derived proteins in the urine of patients with pulmonary TB. A more recent follow-up urinary proteomics study found that a putative molybdopterin biosynthesis protein (Rv1681) was detected in 11 out of 21 TB patients [14].…”
Section: Introductionmentioning
confidence: 99%